Mutations in mitochondrial ATAD3 gene and disease, lessons from in vivo models - Brügel, Marcel; Kiesel, Ann-Sophie; Haack, Tobias B.; Peralta, Susana (Frontiers in Neuroscience, 2024)
Pathogenic variants in the ATAD3 gene cluster have been associated with different neurodevelopmental disorders showing clinical symptoms like global developmental delay, muscular hypotonia, cardiomyopathy, congenital cataracts, and cerebellar atrophy. ATAD3A encodes for a mitochondrial ATPase whose function is unclear and has been considered one of the five most common nuclear genes associated with mitochondrial diseases in childhood. However, the mechanism causing ATAD3-associated disorders is still unknown. In vivo models have been used to identify ATAD3 function. Here we summarize the features of mouse models with ATAD3 loss of function and Drosophila models overexpressing pathogenic ATAD3 variants. We discuss how these models have contributed to our understanding of ATAD3 function and the pathomechanism of the ATAD3-associated disease.